Research on the Interactivity of Video Installation Art in the Digital Era - Wang, Yiying; Fu, Zeya (Transactions on Social Science, Education and Humanities Research, 2023)
With the popularization of digital information technology, new media art has rapidly introduced to China, and various new media art exhibitions with unique themes have emerged in an endless stream, building a bridge between science and technology and art. Interactive technology is based on science and technology, the two collide and blend with each other, and gradually form a new art form, and the interactive video installation art that it has bred is not only an important form of artistic expression, but also the most vital one in new media art, with its unique autonomy and interactivity as a significant feature. This paper aims to explore and study the interaction between video installation art and people.